New scientific opportunities for high pressure research by energy-dispersive XMCD. Issue 3 (2nd July 2016) - Baudelet, F.; Nataf, L.; Torchio, R.
ABSTRACT: XMCD under pressure is used to study the magnetic properties of the transition metal (TM) systems for over 15 years. We present the technique and how it has been developed. The energy dispersive XAS spectrometer is particularly suited for these studies. The effect of pressure on TM magnetism is discussed. Recent studies performed at different edges illustrate the information that can be obtained through XMCD. Finally, some results obtained on TMs are presented, either at the L II, III edges of 5d metals or at the K edge of 3d metals, which correspond to the energy ranges that can be probed when using diamond anvil cells for high pressure. Different cases are treated: pure 3d metals, alloys, magnetic insulator and inorganic compounds.